Effects of Planting Distances and Organic Fertilizer Concentrations on Growth and Yield of Red Onion Plants (Allium ascalonicum L.) - Lince Romauli Panataria; Sri Pratiwi Aritonang; Efbertias Sitorus; Meylin Kristina Saragih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of planting distance and concentration of liquid organic fertilizer on the growth and production of shallots (Allium ascalonicum L.). This study used a Randomized Block Design (RAK) with two treatment factors: planting distance and concentration of liquid organic fertilizer. The treatment factors are as follows: Factor I: Planting Distance (J) consists of 3 treatment levels: J1 = 15 cm x 15 cm; J2 = 20 cm x 20 cm, and J3 = 25 cm x 25 cm. Factor II: Concentration of liquid organic fertilizer (V) consists of 4 treatment levels, namely: V1 = 2 ml / 240 ml of water; V2 = 4 ml / 240 ml of water; V3 = 6 ml / 240 ml of water and V4 = 8 ml / 240 ml of water. Data analysis was done using variance analysis and Duncan’s test. The results showed that planting distance significantly affected the number of leaves, bulb diameter per sample, and fresh bulb weight per sample but had no significant effect on flowering age. POC concentration significantly affected flowering age, tuber diameter per sample, and fresh tuber weight per sample but did not significantly affect plant height and number of leaves. The interaction between planting distance and POC concentration did not significantly affect all observed parameters.